2014
DOI: 10.1007/s10597-014-9712-0
|View full text |Cite
|
Sign up to set email alerts
|

Homelessness, Behavioral Health Disorders and Intimate Partner Violence: Barriers to Services for Women

Abstract: Homeless women comprise a significant portion of the homeless population and may encounter multiple life stressors including mental illness, substance abuse, and trauma. Women who are homeless may experience difficulty gaining access to resources such as shelter and health care. In addition, the interaction of behavioral health problems with intimate partner violence (IPV) may create extraordinary barriers to their engagement in services. This paper explores the co-occurrence of homelessness, behavioral health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 35 publications
1
18
0
1
Order By: Relevance
“…Recent literature on southern homeless women also notes the impact of cycles of poverty, stress, loss of personal relationships and systemic subjection of women's experiences of homelessness ( 22 – 25 ). This literature also highlights the importance of histories of abuse and intimate partner violence in women's pathways to homelessness and as a barrier to seeking services ( 23 , 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent literature on southern homeless women also notes the impact of cycles of poverty, stress, loss of personal relationships and systemic subjection of women's experiences of homelessness ( 22 – 25 ). This literature also highlights the importance of histories of abuse and intimate partner violence in women's pathways to homelessness and as a barrier to seeking services ( 23 , 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…8-10 Thus most studies addressing homeless women's SUD strongly indicate the need to consider the burden of past trauma, IPV, mental health, and health conditions to understand SUD. 11 …”
Section: Introductionmentioning
confidence: 99%
“…The intervention successfully decreased danger and was rated positively by 82% of the women. Peer mentors, those who have experienced IPV and homelessness in the past, have been used to give women an attainable goal for the future and a plan of action (Ponce, Lawless, & Rowe, ). No article could be found that mentioned budgeting, money management, or networking mentorship for women who have experienced IPV.…”
Section: Discussionmentioning
confidence: 99%